THE USE OF SMS TECHNOLOGY AS A TOOL FOR DIRECT MARKETING - Hanson Costa, Dennis (2013)
This article deals with how a new telecommunications technology was adopted as a new direct marketing media, while at the same time discussing new technology adoption by the market, some aspects of the marketing of breakthrough technologies and more specifically direct marketing.